2008
DOI: 10.1142/s0192415x08006235
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between San-Huang-Xie-Xin-Tang and Its Herbal Components on the Gene Expression Profiles in HepG2 Cells

Abstract: Traditional Chinese medicine (TCM) has been used for thousands of years. Most Chinese herbal formulae consist of several herbal components and have been used to treat various diseases. However, the mechanisms of most formulae and the relationship between formulae and their components remain to be elucidated. Here we analyzed the putative mechanism of San-Huang-Xie-Xin-Tang (SHXXT) and defined the relationship between SHXXT and its herbal components by microarray technique. HepG2 cells were treated with SHXXT o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Microarray data show that SHXXT exhibits an anti-proliferation effect via p53 and DNA damage signaling pathways. Moreover, Rhizoma Coptis shares a similar gene expression profile with SHXXT, suggesting that Rhizoma Coptis is the principle herb that exerts the major effect in SHXXT (Cheng et al, 2008). EGb 761, a well-defined extract from Ginkgo biloba, has been widely used in patients with cerebral disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Microarray data show that SHXXT exhibits an anti-proliferation effect via p53 and DNA damage signaling pathways. Moreover, Rhizoma Coptis shares a similar gene expression profile with SHXXT, suggesting that Rhizoma Coptis is the principle herb that exerts the major effect in SHXXT (Cheng et al, 2008). EGb 761, a well-defined extract from Ginkgo biloba, has been widely used in patients with cerebral disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Vanillin has been reported to inhibit mutagenesis induced by chemical and physical mutagens and to suppress the invasion and migration of cancer cells (Lirdprapamongkol et al, 2005;Cheng et al, 2008;Liang et al, 2009). It also displays chemopreventive effects in multiorgan carcinogenesis and hepatocarcinogenesis models in rats (Akagi et al, 1995).…”
mentioning
confidence: 99%
“…Such a transcriptomic approach has been used to study the biological effect of CHM in a wide range of conditions, from cancer to fibrosis, and gastrointestinal, neurological, metabolical and immune disorders (Cheng et al, 2008;Efferth et al, 2011;Guo et al, 2010;Kang et al, 2005;Meng et al, 2010;Pan-Hammarström et al, 2006;Sakai et al, 2007;Sun et al, 2008;Watanabe-Fukuda et al, 2009;Wang et al, 2011a,b,c;Yin et al, 2004;Zhuang et al, 2004). An interesting recent development in the use of transcriptomics indicated that this method can be used as a platform for translational research in CHM, by comparing the transcriptomic patterns with genetic databases of drug-altered genes (Lamb, 2007), drug metabolism-related genes and toxicityassociated genes (Hayes et al, 2005).…”
Section: Development Of the Use Of Omic Techniques In Tcm Researchmentioning
confidence: 99%
“…Using a network analysis to visualise the possible relationship between p53 and other regulated genes, it was established that most of them were connected to p53, thus indicating a central role for p53 in the apoptosis-inducing network. Moreover, using hierarchical cluster analysis, it was shown that one of the plants in the formula, Rhizoma Coptis, showed a similar pattern, thus allowing the identification of the likely principal component of the formula for this effect (Cheng et al, 2008).…”
Section: Genomicsmentioning
confidence: 99%